Hallucination As Psychotic Symptom ReflectedIn Aronofsky's Black Swan Movie (2010):A Psychoanalytic Approach - HARINI, FITRIAYU DIAH (2012)
SUMMARY FITRIAYU DIAH HARINI. A320 080 206. HALLUCINATION AS PSYCHOTIC SYMPTOM REFLECTED IN ARONOFSKY'S BLACK SWAN MOVIE (2010): A PSYCHOANALYTIC APPROACH. MUHAMMADIYAH UNIVERSITY OF SURAKARTA. RESEARCH PAPER. 2012. The major problem of this study is to reveal that hallucination can be a psychotic symptom that caused by many problems based on the structural elements and to analyze the play based on the psychoanalytic approach. In analyzing Black Swan the writer uses qualitative method and psychoanalytic approach. The object of the study is Aronofsky's Black Swan released 2010. The writer uses two kinds of data, namely primary and secondary data source. The primary data is Black Swan. While secondary data are the other data which have relationship with the study, such as some biography of the author, the articles from internet, the books and the other relevant information. The benefit of this study is that the research can enrich knowledge of the researcher and other reader who have interest in literary work on movie with a psychoanalytic approach. Aronofsky in Black Swan shows that people have limitation in psyche and they should have a balance between id, ego and superego to get psychological health. Nina Sayers, as the major character describes and shows the effects of psychological disorder in form of hallucination that closely